Overheating calculation methods, criteria, and indicators in European regulation for residential buildings - Attia, Shady; Benzidane, Caroline; Rahif, Ramin; Amaripadath, Deepak; Hamdy, Mohamed; Holzer, Peter; Koch, Annekatrin; Maas, Anton; Moosberger, Sven; Petersen, Steffen; Mavrogianni, Anna; Maria Hidalgo-Betanzos, Juan; et al. (Energy and buildings, 2023)
•Overheating regulations and calculation methods in 26 European countries were compared.•Most of the existing calculation methods are outdated and do not fit climate-proof buildings.•France requires a mixed-mode operation of naturally ventilated households.•The UK developed a heatwave-based calculation approach.•Comfort-based, multi-zonal, and time-integrated calculation approaches are needed. With the ongoing significance of overheating calculations in the residential building sector, building codes such as the European Energy Performance of Building Directive (EPBD) are essential for harmonizing the indicators and performance thresholds. This paper investigates Europe's overheating calculation methods, indicators, and thresholds and evaluates their ability to address climate change and heat events. e study aims to identify the suitability of existing overheating calculation methods and propose recommendations for the EPBD. The study results provide a cross-sectional overview of twenty-six European countries. The most influential overheating calculation criteria are listed the best approaches are ranked. The paper provides a thorough comparative assessment and recommendations to align current calculations with climate-sensitive metrics. The results suggesta framework and key performance indicators that are comfort-based, multi-zonal, and time-integrated to calculate overheating and modify the EU's next building energy efficiency regulations. The results can help policymakers and building professionals to develop the next overheating calculation framework and approach for the future development of climate-proof and resilient residential buildings.